Computational Techniques for three-phase Load Flow Analysis. Issue 1 (June 2019) - Nazaruddin; Mahalla; Fauzi
Abstract: This paper aims to compute a three-phase load flow for balanced load and unbalanced loads conditions. Unbalanced loading can occur if the power demand of each phase is not equal, this happens because the load usage of each phase varies. Three-phase load flow is a study in the electric power system that will provide information on voltage, phase angle, current, power and power losses of each bus on phases a, b and c. Three phase power flow is carried out for operation planning and control of three-phase electric power systems. The imbalance in the electric power system will affect the use of electrical energy, that is, there will be a decrease in voltage received by consumers. Three-phase load flow computing will be done using the Etap version 12.0 software which will be tested on the IEEE 6 bus system. The computational results show that the unbalanced load flow converges on the 2nd iteration of the bus. The IEEE 6 bus system has the largest voltage drop on bus 3 by 3%, 2.9% and 2.2% for each phase a, b and c. The biggest power losses of the IEEE 6 bus system occur in the connecting line between bus 1 with bus 2 which is 32.5 KW, 28.1 KW and 37.1 KW, with total losses of 254.1 KW and 778.5 KVAR.